Cannibalism by damselflies increases with rising temperature. (31st May 2017) - Start, Denon; Kirk, Devin; Shea, Dylan; Gilbert, Benjamin
Abstract : Trophic interactions are likely to change under climate warming. These interactions can be altered directly by changing consumption rates, or indirectly by altering growth rates and size asymmetries among individuals that in turn affect feeding. Understanding these processes is particularly important for intraspecific interactions, as direct and indirect changes may exacerbate antagonistic interactions. We examined the effect of temperature on activity rate, growth and intraspecific size asymmetries, and how these temperature dependencies affected cannibalism in Lestes congener, a damselfly with marked intraspecific variation in size. Temperature increased activity rates and exacerbated differences in body size by increasing growth rates. Increased activity and changes in body size interacted to increase cannibalism at higher temperatures. We argue that our results are likely to be general to species with life-history stages that vary in their temperature dependencies, and that the effects of climate change on communities may depend on the temperature dependencies of intraspecific interactions.